Immigration and Entrepreneurship - Robert W. Fairlie; Magnus Lofstrom (Center for Economic Studies and ifo Institute (CESifo), 2015)
Immigrants are widely perceived as being highly entrepreneurial and important for economic growth and innovation. This is reflected in immigration policies and many developed countries have created special visas and entry requirements in an attempt to attract immigrant entrepreneurs. Not surprisingly, a large body of research on immigrant entrepreneurship has developed over the years. In this chapter we provide an overview of the economics literature with respect to some of the most fundamental immigrant entrepreneurship issues as well as the empirical methods and data used. The main themes we address are immigrant entrepreneurs' contributions to the economy, entrepreneurship differences across groups and group differences in entrepreneurial success.
Keywords: J15; J18; J31; J38; J61; L26; M13; 330; entrepreneurship; self-employment; innovation; immigrants; immigration